The Philippine law on trademark registration and protection & its IRRs comprehensively annotated - Madrilejos, Alberto Manalon (Ambitgoya Books Enterprises, 2010)
A comprehensive and critical analysis and discussion of the current Philippine law on trademark registration and protection and its implementing rules and regulations; a special practical guidebook for students, historians, scholars, teachers, IP law practititoners and all mark users in the Philippines